Analysis of Implementation Chronic Disease Program (PROLANIS) During Pandemic COVID-19 on Primary Health Care - Anna Tirawani Ambarita; Atik Nurwahyuni (Universitas Teuku Umar, 2022)
The PROLANIS program is a health program initiated by BPJS Kesehatan to prevent diabetes mellitus and hypertension complications. According to Riskesdas data, in 2018, there were 1,017,290 people with diabetes mellitus and 658,201 people with hypertension in Indonesia. This research method is qualitative, and the data collection technique uses in-depth interviews with five types of informants and secondary data observations, namely the coverage of active participants and the number of primary health care employees. There are five types of informants: the head of the primary health care, the doctor in charge, the PROLANIS officer at the primary health care, the BPJS Kesehatan officer, and the PROLANIS participant. The target number of PROLANIS controlled before the pandemic was not achieved. The COVID-19 pandemic conditions increasingly made the target number of PROLANIS participants increasingly unattainable because several PROLANIS activities involved not being implemented. Participants fostered in clubs are limited and selected according to the participants' commitment to participating in PROLANIS activities. Primary health care is expected to carry out innovations so that PROLANIS activities can be carried out in other forms that reduce but still control the health status of the trained participants